2017
DOI: 10.1016/j.livres.2017.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Adipose tissue autophagy and homeostasis in alcohol-induced liver injury

Abstract: Alcohol consumption leads to injury in multiple organs and systems, including the liver, brain, heart, skeletal muscle, pancreas, bone, immune system, and endocrine system. Emerging evidence indicates that alcohol also promotes adipose tissue dysfunction, which may contribute to injury progression in other organs and systems. Autophagy is a lysosomal degradation pathway that has been shown to regulate adipose tissue homeostasis and adipogenesis. Increasing evidence also demonstrates that alcohol consumption af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 134 publications
0
14
0
Order By: Relevance
“…Autophagosomes bring the enveloped cargoes to the lysosomes to form autolysosomes where the lysosomal enzymes consequently degrade the cargos [1,2]. Autophagy is generally induced in response to the starvation conditions to generate biomolecules for cell survival purposes [1][2][3]. Autophagic degradation is split into two categories, selective or nonselective.…”
Section: Introductionmentioning
confidence: 99%
“…Autophagosomes bring the enveloped cargoes to the lysosomes to form autolysosomes where the lysosomal enzymes consequently degrade the cargos [1,2]. Autophagy is generally induced in response to the starvation conditions to generate biomolecules for cell survival purposes [1][2][3]. Autophagic degradation is split into two categories, selective or nonselective.…”
Section: Introductionmentioning
confidence: 99%
“…Both an increased level of the lipidated form of LC3 (LC3-II) as an autophagosome marker and a decreased level of ubiquitin-binding scaffold protein p62, also called sequestosome 1(SQSTM1), were observed in obese humans and mice, the combination of which would appear to be consistent with an increase in autophagy activity during adipogenesis (Klionsky et al, 2016; Yoshii and Mizushima, 2017). The level of autophagy activity seems to differ or at least to fluctuate depending on the adipose tissue type, external stimuli, and tissue age (Bluher, 2013; Kosacka et al, 2015; Li and Ding, 2017). Autophagy is activated when white adipocyte is undergoing differentiation to form lipid droplets.…”
Section: Introduction: Autophagy In Adipocytesmentioning
confidence: 99%
“…Adipocytes undergo three major types of autophagy: macroautophagy, macrolipophagy (generally referred as lipophagy), and mitophagy. These occur dynamically depending on browning status (Baerga et al, 2009; Singh et al, 2009b; Zhang et al, 2009; Singh and Cuervo, 2012; Li and Ding, 2017; Ghosh et al, 2018). Both autophagy malfunction and adipocyte dysfunction are clearly connected with the causes of metabolic disorders such as obesity and diabetes (Baerga et al, 2009; Singh et al, 2009b; Zhang et al, 2009; Bjorndal et al, 2011; Singh and Cuervo, 2012; Bluher, 2013; Scheele and Nielsen, 2017; Ghosh et al, 2018).…”
Section: Introduction: Autophagy In Adipocytesmentioning
confidence: 99%
“…In particular, it was observed that the loss of SNX10 gene in mice determined the over-expression of autophagy markers LAMP-2A, Nrf2 and AMPK in alcohol-mediated liver steatosis (77). Furthermore, several studies noticed that alcohol consumption induce adipose tissue atrophy leading to autophagy impairment and block of tissue homeostasis, which lead to development of diseases correlated with development of pathologies affecting several tissue and organs, including liver (78).…”
Section: Autophagy In Liver Pathogenesismentioning
confidence: 99%